On a merging reduction of the process network synthesis problem - Holló Csaba; Blázsik Zoltán; Imreh Balázs; Kovács Z.; Conference for PhD Students in Computer Science (1.) (1998) (Szeged) (1999)
Since the combinatorial version of the process network synthesis (PNS) problem is NP-complete, it is important to establish such methods which render possible the reduction of the size of model. In this work, a new method called merging reduction is introduced which is based on the merging of operating units. The mergeable operating units are determined by an equivalence relation on the set of the operating units, and all of the operating units included in an equivalence class are merged into one new operating unit. This reduction has the following property: an optimal solution of the original problem can be derived from an optimal solution of the reduced problem and conversely. Presentation of this reduction technique is equipped with an empirical analysis on randomly generated problems which shows the measure of the size decrease.
Keywords: Természettudományok; Számítás- és információtudomány